DISEASES OF THE STOMACH (Modern education and development, 2025)
The digestive system, that is, the Gastrointestinal System (GIS), is a system consisting of all organs starting from the mouth to the anus. Therefore, the topics of stomach and stomach diseases are included in the digestive system.Stomach located within the GIS; It has the task of storing, mixing and breaking down foods. The stomach, which is covered with a membrane, contains water, that is, stomach acid. These salt acids contain enzymes that facilitate digestion. The membrane inside the stomach prevents this stomach acid from attacking the stomach wall. However, this situation differs in unhealthy stomachs. Especially high production of stomach acid and sensitivity in the stomach lining indicate that the relationship between acid and membrane is impaired. These deteriorations cause the emergence of some stomach diseases.